Polymer nanomedicines based on micelle-forming amphiphilic or water-soluble polymer-doxorubicin conjugates: Comparative study of in vitro and in vivo properties related to the polymer carrier structure, composition, and hydrodynamic properties - Braunová, Alena; Chytil, Petr; Laga, Richard; Šírová, Milada; Machová, Daniela; Parnica, Jozef; Říhová, Blanka; Janoušková, Olga; Etrych, Tomáš (Journal of controlled release, 2020)
The study compared the physico-chemical and biological properties of a water-soluble star-like polymer nanomedicine with three micellar nanomedicines formed by self-assembly of amphiphilic copolymers differing in their hydrophobic part (statistical, block and thermosensitive block copolymers). All nanomedicines showed a pH-responsive release of the drug, independent on polymer structure. Significant penetration of all polymer nanomedicines into tumor cells in vitro was demonstrated, where the most pronounced effect was observed for statistical- or diblock copolymer-based micellar systems. Tumor accumulation in vivo was dependent on the stability of the nanomedicines in solution, being the highest for the star-like system, followed by the most stable micellar nanomedicines. The star-like polymer nanomedicine showed a superior therapeutic effect. Since the micellar systems exhibited slightly lower systemic toxicity, they may exhibit the same efficacy as the star-like soluble system when administered at equitoxic doses. In conclusion, treatment efficacy of studied nanomedicines was directly controlled by the drug pharmacokinetics, namely by their ability to circulate in the bloodstream for the time needed for effective accumulation in the tumor due to the enhanced permeability and retention (EPR) effect. Easy and scalable synthesis together with the direct reconstitution possibility for nanomedicine application made these nanomedicines excellent candidates for further clinical evaluation.
Keywords: Polymers; voda; doxorubicin; Nanomedicine; micely; hydrodynamika; nosiče léků; polymery; Hydrodynamics; Micelles; Water; Drug Carriers; Doxorubicin; nanomedicína